The study on the diamond growth and morphology from light elements (N-B-H)synergistic doping systems under HPHT. (January 2018) - Sun, Shishuai; Xu, Zhihui; Cui, Wen; Lv, Jiang; Geng, Yaohui; Li, Hui; Jia, Xiaopeng; Ma, Hong-an
Abstract: The NH, NB and NBH co-doped diamond are synthesized at pressures of 5.0–6.0GPa and temperatures of 1300–1650 °C. The reaction pressure and temperatures for the transformation of graphite-to-diamond are significantly increased with the increasing of light elements content in the starting materials. The results of SEM reveal that the major surfaces defect of growth diamond in this study are steps and distort growth reliefs. The presence of re-entrant corner provided by the twinned structure play an important role in the formation of strip and slice diamond morphology.FTIR and XPS measurementsindicate that the special element composition of NH, NB and NBH co-dopeddiamond synthesized from this work will provide important information for the design of high performance diamond related materials. We also discussthe direct correlation between the formation mechanism of the natural diamond and thesynergistic doping effect of N, B, H element. Highlights: The N-H, N-B and N-B-H co-doped diamonds are synthesized via FG methods. The surface morphologies of strip and slice shape of diamonds in our systems is analyzed. The correlation between the formation mechanism of the diamond and the doping of light elements is discussed.